CONCEPT OF DEVELOPING AN INTELLIGENT SYSTEM FOR CONTROL AND OPERATIONAL DIAGNOSTICS OF TECHNOLOGICAL EQUIPMENT CONDITION - Suleimenov, Batyrbek; Sugurova, Laura; Turynbetov, Nurbol; Suleimenov, Alibek (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
The authors propose a concept for developing a system of automated monitoring and on-line diagnostics of main technological equipment conditions. Monitoring and diagnostics system should work along with the automated control system. In this case, the effects of the optimal control and operational forecasting of the process equipment will complement each other and enhance the overall efficiency of the system. The proposed technique for developing diagnostic algorithms with the use of intelligent technologies will speed up their development and improve the accuracy of forecasting.